2012
DOI: 10.2135/cropsci2010.12.0734
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Rice Productivity in West Africa through Genetic Improvement

Abstract: Rice yields have stagnated in West Africa at 1 to 2 Mg ha"^ because of unfavorable rice environments and poor management practices. Interspecific rice cultivars, the New Rice for Africa (NERICA), were developed by crossing Asian rice {Oryza sativa L.) and African rice (O. glaberrima Steud.) to improve upland and lowland rice productivity in resource-poor farmers' fields. This paper provides an overview of recent studies, performed by the Africa Rice Center and its partners, on evaluation of growth and yield pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 42 publications
4
38
0
Order By: Relevance
“…Rice cultivation in both areas was at subsistence levels. Most farmers held small fields, and also (76%) had low yields of 1 -2 t/ha, which is consistent with the results reported for the whole West Africa [25]. Almost all farmers practiced mixed cropping.…”
Section: Discussionsupporting
confidence: 88%
“…Rice cultivation in both areas was at subsistence levels. Most farmers held small fields, and also (76%) had low yields of 1 -2 t/ha, which is consistent with the results reported for the whole West Africa [25]. Almost all farmers practiced mixed cropping.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to results from Asia (Asai et al, 2009;Atlin et al, 2006;Saito et al, 2007), Saito and Futakuchi (2009), Saito et al (2012) identified B6144-F-MR-6-0-0 (an indica variety developed in Indonesia) as a potential donor for improving yield under low-input conditions. Aus257 was identified as early maturing and high yielding, with strong weed-suppressive ability and greater nutrient uptake than NERICA 1 (Saito, 2016;Saito & Futakuchi, 2014).…”
Section: Martinez Et Al (2014) Review Rice Breeding Activities In Latinsupporting
confidence: 71%
“…Genomics tools and approaches, particularly the QTL mapping and comparative mapping offer new possibilities for crop improvement (Paterson, 2012;Saito et al, 2012). Significant progress in rice functional genomics is being made since the completion of the international rice genome sequencing project (Chen et al, 2011) which offers tremendous opportunities for breeders to improve this important crop by molecular breeding.…”
Section:  Non-conventional Approachesmentioning
confidence: 99%